(untitled) (Journal of Engineering, 2024)
This study deals with the morphology and performance properties of a novel thin flat sheet ultrafiltration membrane; Malachite Green (MG) dye filtration behavior was evaluated in the cross-flow filtration system. The prepared membranes included the incorporation of 16 wt. % of polyether sulfone (PES)/DMF and 5 wt.% of Polyethylene Glycol (PEG) via the phase inversion process. Adding PEG decreased the internal concentration polarization, improved the membrane hydrophilicity, changed pore morphologies, and enhanced membrane performance. The SEM and AFM tests were used to characterize the composition and structure of the membrane. With different casting conditions, the membrane shape changed. The effect of membrane thickness (100, 150, and 200) µm and coagulation bath properties temperature (15, 25, and 35) °C and composition DMF (10, 20, 30 %) in water on the fabricated membrane were investigated. To evaluate the membrane filtration performance, the fabricated membranes were applied in an ultrafiltration system to treat Malachite Green dye solution at a concentration of (10 ppm) as a model pollutant. Based on the obtained results, the ideal membrane parameters were150 µm in thickness, 35°C in temperature, and 10% in composition DMF; the removal efficiency was observed to be (94.5%, 93%, and 99.5%) while the permeate flux (45, 35 and 30) LMH, respectively.